Ajugol's upregulation of TFEB-mediated autophagy alleviates endoplasmic reticulum stress in chondrocytes and retards osteoarthritis progression in a mouse model - Jingtao Wu; Heng Yu; Yangcan Jin; Jingquan Wang; Liwen Zhou; Teng Cheng; Zhao Zhang; Binghao Lin; Jiansen Miao; Zhongke Lin (BMC, 2023)
Abstract Background Osteoarthritis (OA), a degenerative disease with a high global prevalence, is characterized by the degradation of the extracellular matrix (ECM) and the apoptosis of chondrocytes. Ajugol, a extract derived from the herb Rehmannia glutinosa, has not yet been investigated for its potential in modulating the development of OA. Methods We employed techniques such as western blotting, immunofluorescence, immunohistochemistry, X-ray imaging, HE staining, and SO staining to provide biological evidence supporting the role of Ajugol as a potential therapeutic agent for modulating OA. Furthermore, in an in vivo experiment, intra-peritoneal injection of 50 mg/kg Ajugol effectively mitigated the progression of OA following destabilization of the medial meniscus (DMM) surgery. Results Our findings revealed that treatment with 50 μM Ajugol activated TFEB-mediated autophagy, alleviating ER stress-induced chondrocyte apoptosis and ECM degradation caused by TBHP. Furthermore, in an in vivo experiment, intra-peritoneal injection of 50 mg/kg Ajugol effectively mitigated the progression of OA following destabilization of the medial meniscus (DMM) surgery. Conclusion These results provide compelling biological evidence supporting the role of Ajugol as a potential therapeutic agent for modulating OA by activating autophagy and attenuating ER stress-induced cell death and ECM degradation. The promising in vivo results further suggest the potential of Ajugol as a treatment strategy for OA progression.